Injuries in elite road cyclists during competition in one UCI WorldTour season: a prospective epidemiological study of incidence and injury burden - Edler, C.; Droste, J.N., Anemüller, R.; Pietsch, A.; Gebhardt, M.; Riepenhof, H. (The Physician and Sportsmedicine, 2023)
To measure and evaluate the extent and characteristics of accidents and injuries in professional cycling competitions at the elite level (UCI WorldTour 2019) during one complete season.